A rotary shadow freeze-drying replica method for the three dimensional view of virus ultrastructure - Hernández, Francisco (1994)
A new rotary-shadowing process to obtain freeze-drying replicas is described for the analysis of virus ultrastructure, using the inner capsid of human rotavirus as a model. The findings corroborate the icosahedral symmetry with an arrangement pattern of capsomers of T=13L.